Translingual pedagogical perspectives: engaging domestic and international students in the composition classroom - Kiernan, Julia, editor; Frost, Alanna, editor; Malley, Suzanne Blum, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2021)
Addresses the movement toward translingualism in writing classrooms and demonstrates pedagogical strategies faculty can take to represent domestic and international students' perspectives. Contributors explore approaches used by diverse programs, insisting traditional strategies need to be reimagined if they are to engage the growing number of diverse learners.--Provided by publisher.
Addressing monolingual dispositions with translingual pedagogy / Shyam Sharma -- "Criteria mapping" activities and the transformation of student-teacher relations in the composition classroom / Daniel V. Bommarito, Emily Cooney -- Unity in diversity: practicing translingualism in first year writing courses / Ming Fang, Tania Cepero Lopez -- Keepin' it real: developing authentic translingual experiences for multilingual students / Norah Fahim, Bonnie Vidrine-Isbell, Dan Zhu -- An integrative translingual pedagogy of affirmation and resource sharing / Gregg Fields -- "Hay un tiempo y un lugar para todo": literacy autobiographies and the cultivation of translingual rhetorical sensibilities / Esther Milu, Mathew Gomes -- Writing on the wall: teaching translingualism through linguistic landscapes / Mark Brantner -- Following labors of recontextualization: toward a pedagogy of translingual mapping / Brice Nordquist -- Writing theory cartoon: toward a translingual and multimodal pedagogy / Xiqiao Wang -- Translingualism as pedagogical methodology for preservice teachers and peer writing consultants in training / Naomi Silver -- A framework for linguistically inclusive course design / Julia Kiernan.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); English language -- Study and teaching (Higher) -- Foreign speakers; Academic writing -- Study and teaching (Higher) -- Social aspects; Multilingualism; Translanguaging (Linguistics)